The boy next door - Quin-Harkin, Janet; Copyright Paperback Collection (Library of Congress) (New York, NY Bantam Books, 1995)
Amber has left Brendan and moved to Wyoming but she meets Rich so now she must decide who holds the key to her heart
1
Keywords: Dating (Social customs) -- Fiction; Moving -- Fiction; Romantic fiction; Wyoming -- Fiction